RPM Test of Mechanical Desiccated Coconut - Agra Izwan; Saipul Bahri Daulay; Sumono Sumono (Jurnal Rekayasa Pangan dan Pertanian, 2016)
This research was done to test the effect of rpm on the effective capacity of the equipment, percentage of material left in the equipment, and yield. This research was using non factorial completely randomized design. It was found that the work capacity of the equipment, percentage of material left in the equipment, and yield on 1125 rpm are 83,128, 12,17%, and 87,83% kg/hr respectively. On 900 rpm are 75.650, 19,33%, and 80,33% kg/hr respectively. On 750 rpm are 70,484, 25%, and 75% kg/hr respectively. The results showed  that number of knife edge had significant effect on percentage of material left in the equipment, and yield and had significant different on the work capacity. The main cost from year one to year seven were Rp. 143,52, Rp. 134,90, Rp. 132,04, Rp. 130,61, Rp. 129,76, Rp. 129,31, and Rp. 128,78 per kg respectively. Break even point from year one to year seven were 1552,55, 835,26, 596,50, 477,32, 405,96, 368,42, 324,75 kg respectively. The result of net present value from 6% of bank rate was Rp. 1.518.446.869,44 which means this business was competent. The internal rate of return was 35,6% which means this business was competent if the bank rate were not more than 35,6%. Keywords : rpm, grater, desiccated coconut